Correlation between Abortion and Infertility among Nonsmoking Women with a History of Passive Smoking in Childhood and Adolescence. (13th August 2014) - Amirkhani, Jila; Yadollah-Damavandi, Soheila; Mirlohi, Seyed Mohammad-Javad; Nasiri, Seyede Mahnaz; Parsa, Yekta; Gharehbeglou, Mohammad
Abstract : The aim of this study is to evaluate the correlation of exposing to the cigarette smoke in childhood and adolescence with infertility and abortion in women. This case-control study evaluated 178 women who had been attended to at the Amir-al-Momenin Hospital in Tehran in 2012-2013. Seventy-eight women with chief complaint of abortion, infertility, and missed abortion and 100 healthy women were considered as case and control groups, respectively. The tool was a questionnaire with two parts. In the first part demographic information was gathered and in the second part the information regarding the history of passive smoking in childhood and adolescence period, abortion, and infertility was gathered. The mean age in case and control groups was 26.24 ± 3.1 and 27.3 ± 4.2 years, respectively. The mean body mass index (BMI) was 25.74 ± 1.38 Kg/m 2 . Abortion rates among passive smoker and nonpassive smoker patients were statistically significant (P = 0.036 ). Based on findings of this study, the experience of being a passive smoker in childhood and adolescence in women will increase the risk of abortion and infertility in the future, which could be the reason to encourage the society to step back from smoking cigarettes.